The Effect of Profitability on Dividend Policy With Liquidity as A Moderating Variable - Fahri Fitriana; Bambang Mahmudi; Enis Khaerunnisa (Jurnal Riset Akuntansi Terpadu, 2023)
This research aims to determine the effect of profitability, which is proxied by REturn On Asset, on dividend policy, which is proxied by the Dividend Payout Ratio, with liquidity, which is proxied by the Curent Ratio, as a moderating variable for companies included in the LQ 45 issuers listed on the BEI for the 2013 - 2022 period. The population used in this research is all companies included in the LQ 45 issuers listed on the BEI for the 2013 - 2022 period. The research sample consisted of 12 companies. The method used in this research is purposive sampling. The data analysis technique used in this research is Moderate Regression Analysis (MRA). The results of this research show that: (1) profitability as proxied by Rturn On Assets influences dividend policy as proxied by the Dividend Payout Ratio. (2) Liquidity as proxied by the Curent Ratio is able to moderate the influence of profitability on dividend policy.